Homework: An Overload on Chinese School Children - Zhang, Jianjun (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: For a long time, the heavy burden of homework of primary and middle school students in China has been perplexing people in all walks of life especially the parents of children. This paper aims to analyze the influence of heavy homework burden on children's physical and mental health, academic development and relationship between school and home, and the causes of these effects. It is hoped that this paper can arouse the attention of primary and secondary school teachers who can take corresponding measures to reduce the burden of primary and secondary homework.